Wwp2 is essential for palatogenesis mediated by the interaction between Sox9 and mediator subunit 25 - Nakamura, Yukio (2011)
Sox9 is a direct transcriptional activator of cartilage-specific extracellular matrix genes and has essential roles in chondrogenesis. Mutations in or around the SOX9 gene cause campomelic dysplasia or Pierre Robin Sequence. However, Sox9-dependent transcriptional control in chondrogenesis remains largely unknown. Here we identify Wwp2 as a direct target of Sox9. Wwp2 interacts physically with Sox9 and is associated with Sox9 transcriptional activity via its nuclear translocation. A yeast two-hybrid screen using a cDNA library reveals that Wwp2 interacts with Med25, a component of the Mediator complex. The positive regulation of Sox9 transcriptional activity by Wwp2 is mediated by the binding between Sox9 and Med25. In zebrafish, morpholino-mediated knockdown of either wwp2 or med25 induces palatal malformation, which is comparable to that in sox9 mutants. These results provide evidence that the regulatory interaction between Sox9, Wwp2 and Med25 defines the Sox9 transcriptional mechanisms of chondrogenesis in the forming palate.